Variations of the Basal Vein: Identification Using Three-dimensional CT Angiography - Suzuki, Yasuhiro (AJNR Am J Neuroradiol, 2001)
BACKGROUND AND PURPOSE: The basal vein of Rosenthal (BVR) presents with many variations because of its origin in the secondary longitudinal anastomoses between embryonic veins. The variations were evaluated by 3D CT angiography imaging. METHODS: Three-dimensional CT angiograms in the axial stereoscopic view and other directions constructed by the voxel transmission method and maximum intensity projection (MIP) images were obtained in 500 sides of 250 patients. RESULTS: The BVR flowed into the great vein of Galen in 87.8%, but the anastomoses between the first and second segments were not confirmed in 36.9% of this type. The first segments with hypoplastic or aplastic anastomoses flowed into the cavernous sinus or the sphenoparietal sinus. Therefore, typical BVRs with these anastomoses accounted only for 55.4% of all sides. More than one fourth of the typical type also entered the anterior veins such as the cavernous sinus. Drainage was to the lateral mesencephalic vein in 5.6%, peduncular vein in 1.6%, and lateral or medial tentorial sinus in 5.0%. CONCLUSION: Variations of the BVR can be classified on the basis of the five drainage pathways formed during the early embryonic stage. Three-dimensional CT angiography can show the stereoscopic anatomy and the main drainage routes, but not hypoplastic veins, which are only visible on MIP images.